Multi-network data path for 5G mobile multimedia - Li, X.; Salleh, Rosli; Gani, Abdullah; Zakaria, Omar (2009)
The current existing multimedia services have been achieved mainly by fixed internet networks. The 4th Generation (4G) wireless mobile multimedia internet networks integrate with IPv6, LAS-CDMA, OFDM, MC-CDMA, UWB, Networks-LMDS and fixed internet networks to support mobile multimedia services as the same quality of service as fixed internet, which is an evolution not only to move beyond the limitations and problems of 3G, but also to enhance the quality of services, to increase the bandwidth and to reduce the cost of the resource. The 5th wireless mobile multimedia internet networks are real wireless world, which are completed wireless communication without limitation. In this paper, we propose Multi-network data path for 5G real wireless multimedia world.